PENGARUH RETURN SAHAM, VOLUME PERDAGANGAN SAHAM DAN VARIAN RETURN SAHAM TERHADAP BID ASK SPREAD SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERGABUNG DALAM INDEKS LQ 45 PERIODE TAHUN 2003-2005 - Sri Dwi Ari Ambarwati (Jurnal Siasat Bisnis, 2008)
The objective of this research is to test the impact of stock return, stock trading volume and variance of stock return toward bid-ask spread. Using sampling of 20 manufacture companies which are united in LQ 45 index during the period of 2003 until 2005. The compilation of data is done in Jakarta Stock Exchange corner UII, and Indonesian Capital Market Directory (ICMD). The analysis is done with multiple linear regression method, regretted classical assumption examined, f- test and t –test. The result shows that the hypothesis of stock return are rejected, in this result shows that stock return have a positive significant impact toward bid-ask spread while the hypothesis of stock trading volume and variance of stock return are accepted, in this result shows that stock trading volume has a negative significant impact toward bid-ask spread and variance of stock return has a positive significant impact toward bid-ask spread. While as it simultaneously show that stock return, stock trading volume, and variance of stock return have significantly impact toward bid-ask spread and variance of stock return have dominant impact.Key words: Bid-ask spread, multiple linear regression method, stock trading volume, stock return, variance of stock return.